A Construct Validation of the Malaysian University English Test and the English Placement Test: Two High-stakes English Language Proficiency Tests (Malaysian Journal of Learning and Instruction, 2007)
Malaysian students are normally required to show a certain level of English language proficiency before they are offered a place by a local institution of higher learning. One of the examinations conducted to ascertain their level of proficiency is the Malaysian University English Test (MUET). Apart from MUET some universities also conduct their own test for the same reason. This paper discusses a study on the comparability of MUET with the English Placement Test (EPT) conducted by the International Islamic University Malaysia (IIUM). This study was conducted to see whether the two tests could be used interchangeably for admission and placement purposes. The two tests were administered on second year pre university students of IIUM. Analyses show that though significant, the correlation coefficients of the two tests were not high enough for them to be used interchangeably.